Solving the Capacitive Paradox of 2D MXene using Electrochemical Quartz‐Crystal Admittance and In Situ Electronic Conductance Measurements. Issue 1 (8th August 2014) - Levi, Mikhael D.; Lukatskaya, Maria R.; Sigalov, Sergey; Beidaghi, Majid; Shpigel, Netanel; Daikhin, Leonid; Aurbach, Doron; Barsoum, Michel W.; Gogotsi, Yury
<x xml:space="preserve">Abstract</x> Fast ion adsorption processes in supercapacitors enable quick storage/delivery of significant amounts of energy, while ion intercalation in battery materials leads to even larger amounts of energy stored, but at substantially lower rates due to diffusional limitations. Intercalation of ions into the recently discovered 2D Ti3C2Tx (MXene) occurs with a very high rate and leads to high capacitance, posing a paradox. Herein, by characterizing the mechanical deformations of MXene electrode materials at various states‐of‐charge with a variety of cations (Li, Na, K, Cs, Mg, Ca, Ba, and three tetraalkylammonium cations) during cycling by electrochemical quartz‐crystal admittance (EQCA, quartz‐crystal microbalance with dissipation monitoring) combined with in situ electronic conductance and electrochemical impedance, light is shone on this paradox. Based on this work, it appears that the capacitive paradox stems from cationic insertion, accompanied by significant deformation of the MXene particles, that occurs so rapidly so as to resemble 2D ion adsorption at solid‐liquid interfaces. The latter is greatly facilitated by the presence of water molecules between the MXene sheets.